‘Sell[ing] what hasn’t got a name’: An exploration of the different understandings and definitions of ‘community engagement’ work in the performing arts - Mutibwa, Daniel H. (SAGE, 2017)
Widely known to promote broader involvement in the processes which define the arts and culture (Webster, 1997), community engagement work in the performing arts — despite employing a set of commonly recognised norms — has tended to be conceptualised differently both historically and contemporarily. Drawing on ethnographic research — particularly semi-structured qualitative interview accounts of numerous British practitioners with a track record of work in the sector, the article explores these different conceptualisations. The article finds that it is the actual ‘work that matters’ and not what it is named, and that the diversity of understandings and definitions among sectoral practitioners is reflective of evolving thinking, values and practice, something that may be destabilising for better or worse.